2020
DOI: 10.3390/jmse8080594
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Sponge-Derived Microorganisms from Coastal Waters of Central Vietnam

Abstract: Bacteria associated with invertebrates are considered as good sources for biologically active compounds. Sponge-derived bacteria were screened for antimicrobial activities, the presence of the cluster genes of polyketide synthases (PKSs) and non-ribosomal peptide synthetases (NRPSs), and through a colony picking method. Crude extracts of broth cultures were tested for microbial inhibition. Eleven out of 25 isolated strains showed inhibition of at least one of eight tested indicator microorganisms. Antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Meanwhile, a recent whole-genome mining study estimated that a lower percentage (~31%) of Firmicutes carried NRPS and PKS gene clusters [ 30 ]. In a recent study, Mien et al (2020) also reported a lower percentage for NRPS and PKS-I genes (24.0% and 0%, respectively), but higher for PKS-II genes (20.0%), after PCR amplification of 25 marine bacteria isolated from the Central Sea region of Vietnam [ 31 ]. Similarly, a lower percentage of NRPS gene (38%) and PKS-I gene (38%) but a higher percentage of PKS-II (54%) were observed among 50 invertebrate-associated bacteria from the Red Sea [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a recent whole-genome mining study estimated that a lower percentage (~31%) of Firmicutes carried NRPS and PKS gene clusters [ 30 ]. In a recent study, Mien et al (2020) also reported a lower percentage for NRPS and PKS-I genes (24.0% and 0%, respectively), but higher for PKS-II genes (20.0%), after PCR amplification of 25 marine bacteria isolated from the Central Sea region of Vietnam [ 31 ]. Similarly, a lower percentage of NRPS gene (38%) and PKS-I gene (38%) but a higher percentage of PKS-II (54%) were observed among 50 invertebrate-associated bacteria from the Red Sea [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vietnam. These sponges are recognized by their dark brown exterior and yellow interior (Mien et al, 2020;Pham et al, 2013) (Figureure 1).…”
Section: Identification Of Marine Sponge Ra3 and Rb1mentioning
confidence: 99%